Basindustrins transporter via sjöfart och järnväg - En undersökning av beredskapen vid avbrott i norra Sverige - Dahlgren, Fredrik; Forsberg, Mattias (My University, 2013)
Large volumes of cargo are frequently being transported between the northern and southern parts of Sweden both by railroad and sea vessels. If these transport flows suffer disruptions or interruptions there are no alternative paths with the same capacity to which the goods can be reallocated. This indicates a possible vulnerability in the transport-links that may create problems for companies if they have to redirect large flows through other transportation systems. This study has been limited to the heavy industries north of Umeå and the main issue is to examine the flexibility of the transportation infrastructure and how it deal with various disturbances or interruptions. This study also takes into consideration the consequences of disruptions for the heavy industries and it examines how previously interruption has been managed. Furthermore, experienced logisticians have been interviewed, and their answers provide the foundation of the findings in this report. The study shows that heavy industries are exposed to a risk of interruption that in turn may result in increased costs for the affected industry. As soon as affected companies are informed of an interruption in the transportation system they take action. Depending on the level of supply they turn to the spot market to solve their immediate transportation need. Thus, an interruption in the system means that many companies are looking to find alternative transport capacity and a high demand will result in a lack of supply in available cargo carriers. Keeping a constant transport capacity available to enable flexibility in times of excess demand would be a very expensive solution, this because large resources are tied up for long periods of time without being utilized. However, having to reduce production or, in a worst-case scenario, having to completely shut down production, due to lack of transportation capacity would also incur great costs for the heavy industries in the north.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics